Small cell lung carcinoma cell line screen of etoposide/carboplatin plus a third agent. (1st August 2017) - Teicher, Beverly A.; Silvers, Thomas; Selby, Michael; Delosh, Rene; Laudeman, Julie; Ogle, Chad; Reinhart, Russell; Parchment, Ralph; Krushkal, Julia; Sonkin, Dmitriy; Rubinstein, Larry; Morris, Joel; et al.
Abstract: The SCLC combination screen examined a 9‐point concentration response of 180 third agents, alone and in combination with etoposide/carboplatin. The predominant effect of adding a third agent to etoposide/carboplatin was additivity. Less than additive effects occurred frequently in SCLC lines sensitive to etoposide/carboplatin. In SCLC lines with little or no response to etoposide/carboplatin, greater than additive SCLC killing occurred over the entire spectrum of SCLC lines but never occurred in all SCLC lines. Exposing SCLC lines to tubulin‐targeted agents (paclitaxel or vinorelbine) simultaneously with etoposide/carboplatin resulted primarily in less than additive cell killing. As single agents, nuclear kinase inhibitors including Aurora kinase inhibitors, Kinesin Spindle Protein/EG5 inhibitors, and Polo‐like kinase‐1 inhibitors were potent cytotoxic agents in SCLC lines; however, simultaneous exposure of the SCLC lines to these agents along with etoposide/carboplatin, generally, resulted in less than additive cell killing. Several classes of agents enhanced the cytotoxicity of etoposide/carboplatin toward the SCLC lines. Exposure of the SCLC lines to the MDM2 inhibitor JNJ‐27291199 produced enhanced killing in 80% of the SCLC lines. Chk‐1 inhibitors such as rabusertib increased the cytotoxicity of etoposide/carboplatin to the SCLC lines in an additive to greater than additive manner. The combination of GSK‐3 β inhibitor LY‐2090314 with etoposide/carboplatin increased killing in approximately 40% of the SCLC lines. Exposure to the BET bromodomain inhibitor MK‐8628 increased the SCLC cell killing by etoposide/carboplatin in 20–25% of the SCLC lines. Only 10–15% of the SCLC lines had an increased response to etoposide/carboplatin when simultaneously exposed to the PARP inhibitor talazoparib. Abstract : Sixty‐three human small cell lung cancer cell lines were screened to search for agents which may act synergistically with etoposide/carboplatin. Most third agents were additive or antagonistic with etoposide/carboplatin. Third agents which were synergistic are highlighted.